Learning Passing in Volleyball Through a Basic Movement Approach - Sahabuddin, Sahabuddin; Pujianto, Dian; Pratama, Budiman Agung (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This research and development aim to produce a top-passing learning model using a basic movement approach for SMA Negeri 4 Barru class X students. Apart from that, this research and development was carried out to obtain in-depth information about the development and application of the upper passing learning model through a basic movement approach for students and to determine the effectiveness, efficiency, and attractiveness of children towards the model created. This research uses the Research & Development (R & D) research method from Borg and Gall. The subjects in this research and development were students at SMA Negeri 4 Barru, consisting of 30 students. The instruments used in this research and development were questionnaires, as well as volleyball passing test instruments which were used to collect volleyball passing data. The stages in this research and development were: (1) expert evaluation (initial product evaluation); (2) limited trials (small group trials); (3) large trials and (4) main trials (field testing). Test the effectiveness of the model using the top passing test to determine the level of volleyball top passing ability for students before giving treatment in the form of a top passing learning model through the basic movement approach that was developed and to determine the level of top passing ability after the treatment or treatment of the top passing model that was developed, from the initial test carried out obtained an average passing level for students of 19.20, then after being given treatment in the form of a learning model for upper passing through a basic movement approach, an average level of passing ability for students was obtained at 22.80. Furthermore, the most important result from the table above is the t value = 11,641, with df = 29 and significance figure or p-value = 0.000 < 0.05. Thus, it was concluded that there was a significant difference in students' volleyball passes before and after being given the upper passing learning model using a basic movement approach. So this model of learning upper passes using the basic volleyball movement approach is effective in improving learning of upper passing in volleyball for athletes. Based on the development results, it can be concluded that: (1) a volleyball passing pattern model for students, can be developed and applied in volleyball learning; (2) the upper passing learning model through a basic movement approach for students has been developed, evidence of this improvement is shown in the test results of the pre-test and post-test data, there is a significant difference between before and after the model treatment.